Who Are the Losers of IFRS Adoption in Europe? An Empirical Examination of the Cash Flow Effect of Increased Disclosure - Charitou, Andreas; Karamanou, Irene; Lambertides, Neophytos (My University, 2015)
Unlike prior studies that examine the denominator effect, this study investigates the cash flow effect of disclosure as captured by firms exhibiting increases in default risk (DR) around the 2005 mandatory International Financial Reporting Standards (IFRS) adoption in Europe. Using the Merton (1973, 1974) option-based probability of default measure (DR) on a data set of 415 winner firms (with decreases in DR) and 295 loser firms (with increases in DR), we show that loser firms exhibit the same or better financial characteristics in the pre-IFRS adoption period compared with the winner sample. However, after IFRS, loser firms exhibit deteriorating characteristics, with smaller increases in their Tobin's q valuations, greater increases in leverage, and poorer return performance. Logistic analysis suggests that even though in the pre-IFRS period loser firms exhibit greater profitability and analyst following and lower leverage, in the post-IFRS period their profitability is less than that of winner firms while exhibiting similar leverage and analyst following characteristics. Through an examination of the determinants of the change in DR, the results suggest that loser firms incur a greater increase in DR the poorer their home country's legal enforcement environment, the lower their analyst following, and the greater their propensity to manage earnings. In general, our results are consistent with the existence of a significant cash flow effect for the loser sample.
Keywords: Cash flow effect; Default risk; Disclosure; IFRS adoption; Losers